Effect of vegetable proteins on physical characteristics of spray-dried tomato powders. (September 2016) - Tontul, Ismail; Topuz, Ayhan; Ozkan, Ceren; Karacan, Merve
In the present study, the effectiveness of different vegetable proteins (pea protein isolate, soy protein isolate and zein from maize) at two different ratios (1% and 5%) on product yield and physical properties of spray-dried pulpy tomato juice was investigated. Additionally, these proteins were compared with whey protein concentrate which has a superior effect on spray dried products at the same concentrations. Additionally, plain tomato juice was also spray dried for comparison with vegetable proteins. The product yield of the tomato powders dried with the vegetable proteins was lower than with the whey protein concentrate. Among vegetable proteins, the highest product yield was produced with 1% soy protein isolate. In all products, there was a slight colour difference between the reconstituted tomato powders and the raw tomato juice, which indicated that pulpy tomato juice can be spray dried with minor colour change. All powders had unique free-flowing properties estimated as Carr index and Hausner ratio due to their large particles.